2017
DOI: 10.5406/musimoviimag.10.3.0003
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Diegetic/Nondiegetic Distinction in the Film Musical

Abstract: This paper exposes problems with diegetic-nondiegetic distinction as applied to film musicals, arguing that it is inconsistent with its use in other areas of cinema studies and poses problems for appreciating the narratives of these films. As a replacement, the author defines two scalar concepts, one tracking the number's degree of realism, the other its degree of formality.The concept of the "diegetic number" has become as central to scholarship on film musicals as "diegetic music" is to other genres of film.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Robynn Stilwell suggests that ‘many films begin with credit music that is full sounding and apparently non-diegetic but “shrinks” to the diegetic space of the first post-credit scene’ (2007: 197). Discourse around the binary is widely debated in relation to the genre of the film musical (see Altman, 1987; Heldt, 2013; Penner, 2017, Stillwell, 2007). The difficulty of maintaining this binary is pronounced within film musicals for obvious reasons: whilst each film may differ in terms of approach and effect, the general conventions of the genre dictate that songs function as a key component within the diegetic narrative of the fiction, despite often being accompanied by orchestration within the non-diegetic sphere.…”
Section: Crossing the Line: Trans-diegetic Addressmentioning
confidence: 99%
See 4 more Smart Citations
“…Robynn Stilwell suggests that ‘many films begin with credit music that is full sounding and apparently non-diegetic but “shrinks” to the diegetic space of the first post-credit scene’ (2007: 197). Discourse around the binary is widely debated in relation to the genre of the film musical (see Altman, 1987; Heldt, 2013; Penner, 2017, Stillwell, 2007). The difficulty of maintaining this binary is pronounced within film musicals for obvious reasons: whilst each film may differ in terms of approach and effect, the general conventions of the genre dictate that songs function as a key component within the diegetic narrative of the fiction, despite often being accompanied by orchestration within the non-diegetic sphere.…”
Section: Crossing the Line: Trans-diegetic Addressmentioning
confidence: 99%
“…In this sense, unless all songs are rendered ‘realistically’ through, for example, characters playing on screen instruments, characters/viewers are faced with a conflation of the non-diegetic/diegetic space. Nina Penner suggests that: ‘Observing the different conventions governing film musicals in contrast to most other genres of film, some scholars have concluded that the diegetic/nondiegetic distinction is inapplicable to this genre’ (2017: 6) and how ‘in the context of non-musical films, there is at least a consensus about how this distinction ought to be understood’ (Penner, 2017: 15).…”
Section: Crossing the Line: Trans-diegetic Addressmentioning
confidence: 99%
See 3 more Smart Citations